The Influence of Compensation on Employee Performance Mediated by Job Satisfaction Among Sales Department Employees at PT SBC Ngoro Jombang - Arrahima, Irea (CV. Proaksara Global Transeduka, 2024)
This study aims to understand and explain the influence of compensation on employee performance through job satisfaction among sales department employees at PT SBC Ngoro Jombang. The research method used is path analysis with t-tests and Sobel tests to examine the direct and indirect relationships between compensation, job satisfaction, and employee performance at PT SBC Ngoro Jombang. The population of the study consists of all sales department employees at PT SBC Ngoro Jombang, with a sample of 65 people selected using census technique. The data source is primary data obtained from the distribution of questionnaires. Based on the analysis results, it can be concluded that: First, compensation has an effect on the performance of sales department employees at PT SBC Ngoro Jombang. Second, compensation affects job satisfaction of sales department employees at PT SBC Ngoro Jombang. Third, job satisfaction influences the performance of sales department employees at PT SBC Ngoro Jombang. Fourth, compensation affects employee performance through job satisfaction among sales department employees at PT SBC Ngoro Jombang.